Computing with the COM-Poisson Distribution - Minka, Tom; Shmueli, Galit; Kadane, Joseph B.; Borle, Sharad; Boatwright, Peter (2003)
The Conway-Maxwell-Poisson (COM-Poisson) is a generalization of the Poisson distribution which can model both under-dispersed and over-dispersed data. However, the distribution, moments, and MLE cannot be computed in closed form. This paper describes computational schemes and handy approximations for the COM-Poisson.